A College For Appalachia : Alice Lloyd on Caney Creek - Searles, P. David, 1933- (Book collections on Project MUSE., 2015)
Alice Spencer Geddes Lloyd was a New England woman with a mission in life. In 1916 she settled on Caney Creek in Eastern Kentucky, determined to bring higher education to this remote corner of Appalachia. The school she founded, now Alice Lloyd College, continues to serve the area and its people and to stand as a tribute to Lloyd's remarkable energy, determination, and vision. Lloyd's program combined a rigorous academic curriculum with an intense effort to instill a sense of service in the school's graduates. This education was provided free and required only that the students abide by Lloyd's.